Outcomes of Follow-up Imaging After Pediatric Spinal Trauma Confirmed With Magnetic Resonance Imaging - Sirén, Aapo (Lippincott Wolters Kluwer, 2025)
Background: Imaging plays a crucial role in the diagnostic workup of pediatric spinal trauma. Computed tomography and conventional radiographs are widely used as the primary imaging methods. Magnetic resonance imaging (MRI) is a radiation-free alternative with high sensitivity for bony and soft tissue injuries. There is no consensus on the optimal use of follow-up imaging in pediatric spinal trauma without immediate surgical treatment, especially if the injury is primarily confirmed with MRI. This study aimed to assess the diagnostic value of follow-up imaging after MRI-confirmed spinal trauma in children.
Methods: The medical records and the imaging data of children and adolescents with emergency spinal MRI and follow-up imaging over 8 years were retrospectively reviewed. The primary study outcome was the outcome of follow-up imaging and its effect on management.
Results: The study population consisted of 127 patients. The follow-up imaging did not alter the management in any patient with presumably stable injury in emergency MRI. Short-term follow-up imaging showed no clinically significant progression in thoracolumbar compression fractures. Flexion-extension radiographs had no additional value in cases with stable cervical spinal injury on emergency MRI.
Conclusions: The clinical utility of short-term follow-up imaging is low in children with stable spinal injury on emergency MRI.